Async & performance - Simpson, Kyle, (JavaScript systems architect), ....- (Beijing : O'Reilly, 2015)
No matter how much experience you have with JavaScript, odds are you don't fully understand the language. As part of the "You Don't Know JS" series, this compact guide focuses on the new asynchronous features in JavaScript, which are often confusing to developers. You'll learn about promises, generators, and coroutines, all of which allow you to create more sophisticated single-page web applications that provide the features of a desktop application without tying up the user's browser.
Keywords: JavaScript (Computer program language).